Convivenza delle diversità, pluralismo religioso e universalità dei diritti. Modelli di approccio. Indicazioni metodologiche (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Esperienze storiche e modelli di approccio alle diversità culturali - 2. Elementi caratterizzanti l’esperienza italiana - 3. Convivenza delle diversità: indicazioni per una metodologia. In particolare, l’eredità della lezione maritainiana - 4. L’ambito scolastico come luogo specificamente vocato all’educazione alla convivenza interreligiosa.Abstract. The paper highlights the limits of the most well-known models of approach to cultural diversities, the assimilationist one and the communitarian one, which are typical, respectively, of France and England and of their colonial history. Italy has not remarkable colonial traditions and so it can be more free from the weight of the past in developing strategies able to face up to the problems of the multi-ethnic and multi-religious societies. Starting from the basic principles of pluralism and secularism (principio supremo di laicità, according to the words of Italian Constitutional Court), are examined the “Carta dei valori della cittadinanza e dell’integrazione” (15th June 2007) and the recent “Patto nazionale per un Islam italiano” (1st of February 2017). From a more general point of view, the paper describes and supports the thesis of Jacques Maritain about the foundation of human rights, the basis of a peaceful coexistence in a pluralistic society. Finally, it deals with the issue of teaching about religion and history of religions in Italian public schools. These kinds of courses should help students to get to know the religions present in our country - both the historical ones and the “new” ones, coming from the recent processes of immigration - in order to promote and increase the mutual respect and the inter-cultural dialogue.